Temporal Dynamics of Gene Expression During Endothelial Cell Differentiation From Human iPS Cells: A Comparison Study of Signalling Factors and Small Molecules - Belt, Heini; Koponen, Jonna K.; Kekarainen, Tuija; Puttonen, Katja A.; Mäkinen, Petri I.; Niskanen, Henri; Oja, Joni; Wirth, Galina; Koistinaho, Jari; Kaikkonen, Minna U.; Ylä-Herttuala, Seppo (Frontiers in Cardiovascular Medicine, 2018)
Endothelial cell (EC) therapy may promote vascular growth or reendothelization in a variety of disease conditions. However, the production of a cell therapy preparation containing differentiated, dividing cells presenting typical EC phenotype, functional properties and chemokine profile is challenging. We focused on comparative analysis of seven small molecule-mediated differentiation protocols of ECs from human induced pluripotent stem cells. Differentiated cells showed a typical surface antigen pattern of ECs as characterized with flow cytometry analysis, functional properties, such as tube formation and ability to uptake acetylated LDL. Gene expression analysis by RNA sequencing revealed an efficient silencing of pluripotency genes and upregulation of genes related to cellular adhesion during differentiation. In addition, distinct patterns of transcription factor expression were identified during cellular reprogramming providing targets for more effective differentiation protocols in the future. Altogether, our results suggest that the most optimal EC differentiation protocol includes early inhibition of Rho-associated coiled-coil kinase and activation of cyclic adenosine monophosphate signaling, and inhibition of transforming growth factor beta signaling after mesodermal stage. These findings provide the first systematic characterization of the most potent signalling factors and small molecules used to generate ECs from human induced pluripotent stem cells and, consequently, this work improves the existing EC differentiation protocols and opens up new avenues for controlling cell fate for regenerative EC therapy.